Effect of early reflections on difficulty of listening to speech in noise and reverberation - Sato, Hiroshi; Bradley, John S.; Morimoto, Masayuki (Canadian Acoustics, 2002)
The effect of early reflections on the speech intelligibility in the presence of noise reverberation was examined. Listening tests were performed to assess the word intelligibility and perceive the difficulty of listening to speech in simulated sound fields. The tests showed that the early reflections improved subjective ratings of speech transmission by increasing the signal-to-noise ratio.